The Relationship Between Age, Gender, Workload, and Complaints of Low Back Pain (LBP) among Emergency Room Nurses - Ahmad Dimas Dimyati; Marthia Ikhlasiah; Ismarina (KHD Production, 2024)
Low Back Pain (LBP) is Pain felt in the lower back area, can be local pain or radicular pain or both. Risk factors for low back pain (LBP) include age, gender and workload. This study aims to determine the relationship between age, gender and workload with complaints of Low Back Pain (LBP) in nurses in the emergency department of RSUD Banten in 2022. This type of correlation research uses a cross-sectional study approach. The population in this study were all ER nurses at Banten Regional Hospital as many as 65 nurses. The number of samples was determined by a total sampling technique of 65 respondents. The results showed 33 (50.8%) nurses had mild LBP complaints, 35 (53.8%) nurses aged < 30 years, 40 (61.5%) female nurses and 38 (58.5%) nurses had a light workload. The results of the analysis showed that there was a relationship between age and complaints of LBP (P value 0.004), gender with complaints of LBP (P value 0.002) and workload with complaints of LBP (P value 0.000). It is expected that the Banten Regional Hospital will observe and treat nurses who have LBP complaints.